ECONOMIC EFFICIENCY OF ICEBERG LETTUCE GROWING IN THE FUTURE PERIOD (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article presents information on research, economic efficiency and productivity of lettuce varieties at the Research Institute of Vegetable, Melon Crops and Potato in 2020-2022.